Yabancı dil ders kaygısının farklı örneklemlerde ve gelişimsel açıdan incelenmesi - Tuncer, Murat; Akmençe, Ahmet Egemen (My University, 2018)
The general aim of this research is to investigate anxiety of foreign language lessons in different samples developmentally. In the research conducted through the screening model, the Foreign Language Course Anxiety scale was used as the data collection tool. The research for which high school and university students were chosen as sample One-way analysis of variance, Mann Whitney U test, Kruskall Wallis H test, Correlation and Regression analysis were used to analyze the data. As a result of the research, it was determined that the students who constituted the sample had low level of foreign language lesson in general and education background of the parents at high school level did not make any significant difference. A significant difference was found in the sub-dimension of speaking with foreigners in terms of mother education status at undergraduate level. Regression analysis for the undergraduate level revealed that speech anxiety in Language Courses explain 89% of the total variance and when the sub-dimension of Interest in Foreign Language Couse is added, it explains 93% of the variance. Similar results were obtained at the high school level. As a result of the research, it is considered that the students who have reasonable level of anxiety can motivate the students and increase their gains. Making foreign languages a tool for the students to use in real life and allowing them to communicate with people speaking native English or speaking English as second languages will increase their interest in the target language. Especially in language lessons, planning and encouraging speech activities will have a positive effect on anxiety.

Bu araştırmanın genel amacı yabancı dil ders kaygısının farklı örneklemlerde gelişimsel olarak araştırılmasıdır. Tarama modeline göre yürütülen araştırmada veri toplama aracı olarak Yabancı Dil Ders Kaygısı ölçeği kullanılmıştır. Lise ve üniversite öğrencilerinin örneklem olarak seçildiği araştırmada veriler tek yönlü varyans analizi, Mann Whitney U testi, Kruskall Wallis H testi, Korelasyon ve Regresyon analizine göre çözümlemiştir. Araştırma sonucunda örneklemi oluşturan öğrencilerin genel olarak yabancı dil ders kaygılarının düşük olduğu, sınıf ve lise düzeyi, anne ve baba eğitim durumunun anlamlı düzeyde fark yaratmadığı belirlenmiştir. Lisans düzeyinde anne eğitim durumu açısından yabancılarla konuşma kaygısı alt boyutunda anlamlı düzeyde fark bulunmuştur. Lisans düzeyi için yapılan regresyon analizinde dil dersinde konuşma kaygısının toplam varyansın %89’unu, dil dersine yönelik ilgi alt faktörü eklendiğinde ise %93’ünün açıklanabildiği görülmüştür. Lise düzeyinde de buna benzer sonuçlar elde edilmiştir. Araştırma sonucunda makul seviyede kaygının öğrenciyi motive edip kazanımları arttırabileceği düşünülmektedir. Öğrencilerin yabancı dili gerçek hayatta kullanabilecekleri bir araç hâline getirmek ve onlara ana dili veya yabancı dili İngilizce olan kişilerle iletişim kurmasına imkân tanımak onların hedef dile ilgisini arttıracaktır. Özellikle dil dersinde konuşma etkinliklerinin planlanması ve teşvik edilmesi kaygı üzerinde etkili olacaktır.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Foreign language course anxiety; English teaching; High school and undergraduate students; Regression analysis; Yabancı dil ders kaygısı; İngilizce öğretimi; Lise ve lisans öğrencileri; Regresyon analizi